Factors associated with patient activation in inflammatory arthritis: a multisite cross-sectional study. (5th November 2021) - Jones, Bethan; Ndosi, Mwidimi; Hunt, Andrew; Harcourt, Diana; Dures, Emma
Abstract: Objectives: Patient activation covers the skills, abilities and behaviour that impact how able and willing someone is to take an active role in self-managing their health. This study explored clinical and psychosocial factors associated with patient activation in rheumatology patients. Methods: This was a cross-sectional study using postal survey methods. Participants with inflammatory rheumatic conditions were from six rheumatology centres in England. Patient activation was captured using the Patient Activation Measure (PAM). Twenty-nine explanatory factors were tested for potential association with patient activation in univariable and multivariable analyses. In preliminary multivariable analyses, factors found to have an association with patient activation at a P < 0.1 level were entered into the final multivariable model. Those that remained significant at a P < 0.05 level were considered associated with patient activation. Results: The sample comprised 251 participants (74% female) with a mean age of 59.31 years (s .d . 12.69), disease duration of 14.48 years (s .d . 12.52) and a PAM score of 58.3 (s .d . 11.46). Of the 29 candidate factors, 25 were entered into a preliminary multivariable analysis. In the final multivariable analysis, four factors (self-efficacy, the illness belief that treatment will control participants' condition and two dimensions of health literacy) were significantly associated with patient activation. This final model accounted for 40.4% of the variance in PAM scores [F(4, 246) = 41.66, P < 0.001]. Conclusions: Patient activation is important in managing rheumatic conditions. Our data confirm that self-efficacy and health literacy are particular targets for patient activation interventions.